Численное исследование обтекания турбинных решеток профилей. Часть 1. Верификация расчетного метода - Хомылев, С. А.; Резник, С. Б.; Ершов, С. В. (НТУ "ХПИ", 2008)
Представлено результати чисельного модулювання плоскої течії у двох турбінних решітках, виконано порівняння результатів розрахунку з експериментом. Розрахунки було проведено з використанням програмного комплексу FlowER. Було одержано задовільний збіг розрахункових та експериментальних даних.

The article represents the results of numerical investigations of a 2-D gas flow in two different linear turbine cascades, the results of CFD calculations are compared with the experimental data. Numerical investigations are executed using the CFD code FlowER. Numerical results and experimental data are in good agreement.
Numerical investigation of flow in linear turbine cascades. Part 1. Verification of numerical method
Keywords: вязкий газ; уравнения Навье-Стокса; программный комплекс FlowER; моделирование